PERAN RELAWAN YAYASAN KAKAK AMAN INDONESIA DALAM MENUMBUHKAN SIKAP BERANI BERSUARA TERHADAP KEKERASAN SEKSUAL - Jibran Alfaruq, Muhammad; Pertiwi, Fitri; Siregar, Herlina; Fatimah, Nining (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sexual violence against children and adolescents remains a serious problem that often goes unreported due to social stigma, fear, and low awareness of victims to report. In this context, the role of volunteers from the Indonesian Safe Brother Foundation is crucial in fostering the courage to speak up as a form of self-protection. This study aims to analyze the role of volunteers in providing education and building children's courage to disclose experiences of sexual violence. This study uses a qualitative approach with a case study, while data collection techniques include in-depth interviews and observations. The main research subjects included three volunteers and three elementary school children who were the targets of the education program. The results show that volunteers play a crucial role as educational agents in building children's courage to speak up. Through a child-friendly and participatory approach, volunteers successfully increased children's understanding of body boundaries, types of sexual violence, and self-protection steps such as